2019
DOI: 10.1177/0963689719835192
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Progenitor Cells Conditioned Medium Supports Number of GABAergic Neurons and Exerts Neuroprotection in Cultured Striatal Neuronal Progenitor Cells

Abstract: There is growing evidence that stem and progenitor cells exert regenerative actions by means of paracrine factors. In line with these notions, we recently demonstrated that endothelial progenitor cell (EPC)-derived conditioned medium (EPC-CM) substantially increased viability of brain microvascular cells. In the present study, we aimed at investigating whether EPC-CM supports cell survival of cultured striatal progenitor cells. For that purpose, primary cultures from fetal rat embryonic (E14) ganglionic eminen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 63 publications
4
12
0
Order By: Relevance
“…Further experiments will be needed to verify whether EPC-CM promotes the proliferation of immature neurons in cortical cultures and to evaluate the possible role of lipids and other factors. On the other hand, the finding that EPC-CM induced a prominent increase of microglia cell numbers was not surprising and in line with our past report 7 . In fact, we have previously reported that several immunomodulatory cytokines are secreted from EPC 7 , 8 .…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Further experiments will be needed to verify whether EPC-CM promotes the proliferation of immature neurons in cortical cultures and to evaluate the possible role of lipids and other factors. On the other hand, the finding that EPC-CM induced a prominent increase of microglia cell numbers was not surprising and in line with our past report 7 . In fact, we have previously reported that several immunomodulatory cytokines are secreted from EPC 7 , 8 .…”
Section: Discussionsupporting
confidence: 91%
“…Notably and to our knowledge for the first time, we could demonstrate that EPC-CM disclosed the capacity to confer neuroprotection from a metabolic insult. These results extend our previous observations regarding survival-promoting capacity of paracrine factors released by peripheral blood-derived EPC on striatal and ventral mesencephalic neuronal cells 7 8 . The mechanisms and pathways involved in higher GABA-ir cell densities found with EPC-CM supplementation in cultures challenged by GSD, however, were not addressed in the present study.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations